2012
DOI: 10.4025/actasciagron.v34i2.13043
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high dilutions of Pulsatilla nigricans on the vigour of soybean seeds subjected to accelerated aging

Abstract: ABSTRACT. The aim of this study was to evaluate the effect of high dilutions of Pulsatilla nigricans in dinamisations 6, 12, 18, 24 and 30 CH on the vigour of soybean seeds subjected to accelerated aging. The experiment was conducted according to a randomised design with 6 treatments and 10 replicates. The treatments consisted of dinamisations 6, 12, 18, 24 and 30 CH and a distilled-water control. After the treatments, the seeds were subjected to accelerated aging (48h at 42ºC) in a growth chamber (25 ± 2ºC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
1
2
0
2
Order By: Relevance
“…Medium followed by the same letter in the column do not differ significantly from each other by Tukey test at 5% probability. Similar to the results of this study, Silva et al (2012) also found that dilutions between 18CH and 30CH provided promising results for the effect of soybean seeds, while aerial part length values for the dilutions 6CH and 24CH did not differ from the control, being responses to the present study. In contrast, Marques et al (2008) reported an increase in the length of the aerial part of the plant spontaneous Sida rhombifolia, studying the dynamizations of 3CH, 6CH, 12CH and 30CH with use of homeopathic preparations of Cymbopogon winterianus.…”
Section: Resultssupporting
confidence: 90%
“…Medium followed by the same letter in the column do not differ significantly from each other by Tukey test at 5% probability. Similar to the results of this study, Silva et al (2012) also found that dilutions between 18CH and 30CH provided promising results for the effect of soybean seeds, while aerial part length values for the dilutions 6CH and 24CH did not differ from the control, being responses to the present study. In contrast, Marques et al (2008) reported an increase in the length of the aerial part of the plant spontaneous Sida rhombifolia, studying the dynamizations of 3CH, 6CH, 12CH and 30CH with use of homeopathic preparations of Cymbopogon winterianus.…”
Section: Resultssupporting
confidence: 90%
“…With the available capture tools (GDV and BSL) and image analysis, observed dif-ferences between the effects of UHD treatments would support studies of the intrinsic mechanisms of these substances in the seeds. Sucussed ultra dilutions partly explain similarities to specific instructional loads in plant cells in their unique characteristics, when compared to autonomous intelligent units (Silva et al, 2012). Table 4.…”
Section: Gdv and Bsl Imagesmentioning
confidence: 99%
“…Representatives of the Ranunculaceae family are highly valued for their multiple usefulness for humans, and due to long-term growth and relative longevity of populations they are of great importance in the natural environment (Antoń and Kamińska 2015;da Silva et al 2012;Hao et al 2015;Jiang et al 2017;Deng et al 2019). In addition to high value in nature (Bochenková et al 2012(Bochenková et al , 2015, Pulsatilla species have medicinal properties (Danova et al 2009;Hao et al 2015;Lin et al 2011;.…”
Section: Introductionmentioning
confidence: 99%